Review of situation of Hedeoma multiflora Benth (Peperina de las lomas): an aromatic - medicinal Argentine species at risk - Peralta, Patricia Angelica; Guariniello, Julian; Escandon, Alejandro Salvio (Universidad de Santiago de Chile, 2020)
Aromatic and medicinal plants (AMPs) have great potential for the synthesis of secondary metabolites, which are used by the pharmaceutical and food industry. In addition, they are part of ancestral medicine and the livelihood of many families in regional economies. Argentina has a high number of AMPs. However, the intensive extraction system (overexploitation), together with other anthropic actions, puts them at risk. The "peperina de las lomas" (Hedeoma multiflora Benth. (Lamiaceae)) is within this problem. This native species, xerophyte, is distributed in central Argentina, in stony mountain areas, forming small bushes. In this work, the existing information of the species was collected, covering from its environmental problems to the most recent investigations, oriented towards its conservation and the development of its germplasm. These data will serve to promote activities aimed at preventing the degradation of this resource and promoting its sustainable use. Las plantas aromáticas y medicinales (PAMs) tienen un gran potencial para la síntesis de metabolitos secundarios, los cuales son utilizados por la industria farmacéutica y alimentaria. Además, son parte de la medicina ancestral y el sustento de muchas familias de las economías regionales. Argentina posee un alto número de PAMs. Sin embargo, el sistema de extracción intensivo (sobreexplotación), junto a otras acciones antrópicas, las coloca en riesgo. La “peperina de las lomas” (Hedeoma multiflora Benth. (Lamiaceae)) se encuentra dentro de esta problemática. Esta especie nativa, xerófita, se distribuye en el centro de Argentina, en zonas pedregosas serranas, formando pequeñas matas. En este trabajo se recopiló la información existente de la especie abarcando, desde su problemática ambiental hasta las investigaciones más recientes, orientadas a su conservación y al desarrollo de su germoplasma. Estos datos servirán para promover actividades destinadas a evitar la degradación de este recurso y propiciar su aprovechamiento sustentable.